Nutrition risk assessed by nutritional risk screening 2002 is associated with in-hospital mortality in older patients with covid-19 - KOCAKAYA, DERYA; TUFAN ÇİNÇİN, ASLI (My University, 2022)
Background Although numerous studies have been performed to determine predictors of coronavirus disease 2019 (COVID-19) mortality, studies that address the geriatric age group are limited. The aim of this study was to investigate the utility of the Nutritional Risk Screening 2002 (NRS-2002) and the Geriatric 8 (G8) screening tools in predicting clinical outcomes in older adults hospitalized with COVID-19. Methods Patients aged >= 60 years who were hospitalized with COVID-19 in the second wave of the pandemic were included in the study. COVID-19 infection was demonstrated by a positive real-time reverse transcriptase-polymerase chain reaction on nasopharyngeal swab or positive radiological findings. Disease severity was determined as defined by the National Institutes of Health. Patient demographics, laboratory values on admission, comorbidities, and medications were recorded. The NRS-2002 and the G8 screening tools were performed for all patients by the same geriatrician. Primary outcome was in-hospital mortality. Results A total of 121 patients were included. Mean age was 75 +/- 9 years, and 51% were female. Mean body mass index was 27 +/- 4.5 kg/m(2). Sixty-nine percent of the patients had nutrition risk according to the NRS-2002. Eighty-nine percent of the patients had a G8 score <= 14. In-hospital mortality occurred in 26 (22%) patients. Older age and having nutrition risk as determined by the NRS-2002 were independently associated with a higher risk of in-hospital mortality in older patients with COVID-19. Conclusion The NRS-2002 tool provides rapid assessment for risk stratification in hospitalized older patients with COVID-19.
Keywords: Sağlık Bilimleri; Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Health Sciences; Nutrition and Dietetics; Agricultural Sciences; Agriculture; BESLENME VE DİYETETİK; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); NUTRITION & DIETETICS; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); Beslenme ve Diyetetik; COVID-19; hospital mortality; nutrition risk; nutrition status; older adults; MALNUTRITION; VALIDATION; NRS-2002; CANCER; TOOL; COVID‐19; hospital mortality; nutrition risk; nutrition status; older adults